Nebulised cromoglycate, theophylline, and placebo in preschool asthmatic children. Issue 8 (August 1981) - Glass, J; Archer, L N; Adams, W; Simpson, H
Abstract : Sixteen children aged under 5 years with chronic asthma completed a double-blind crossover trial of treatment with oral choline theophyllinate (6.7 mg/kg four times daily) and nebulised sodium cromoglycate (20 mg four times daily). The trial comprised three 8-week treatment periods during which active sodium cromoglycate, active choline theophyllinate, and placebo were given in random order. Symptom scores for sleep disturbance, cough, wheeze, and daily activities were similar during the three treatment periods if results were analysed using Friedman's non-parametric analysis of variance. However the Mantel-Haenszel test showed that sodium cromoglycate was superior to placebo (P less than 0.05) in maintaining normal daily activities. Either regimen is safe and well tolerated by young children.